The Evaluation of Changes in the Center of Pressure in Different Types of Defense on the Professional Volleyball Players - Elaheh Azadian; Nasrin Eftekhari; Rafe Mohammad Zaheri (Biyumikānīk-i varzishī, 2022)
Objective The purpose of the present study was to investigate the center of pressure (CoP) movements during the jump-landing while defending on the net in professional volleyball players and compare it with beginner volleyball players. Methods In this research, 10 professional volleyball players and 10 beginner volleyball players voluntarily participated in this study. The CoP movements in anterior-posterior (AP) and medial-lateral (ML) directions in 5 forms of volleyball net defense skills including static jump, right and left side step, right and left long cross step by using Vicon three-dimensional motion analysis machine and two Kistler force plates were measured. Results In the jumping-phase of static jump, left side step jump and left long cross step jump, there was a significant difference in CoP movements and in the AP direction (p < 0.05), but in right side step jump, there was a significant intergroup difference in CoP movements in the direction of AP and ML (p < 0.05). In the landing phase, there was a significant difference between the two groups in the AP direction in the right side step jump and left long cross step jump (p < 0.05). Conclusion Beginners are exposed to more musculoskeletal injuries due to greater CoP movement in both AP and ML directions. Failure to control the CoP movement may lead to a fall during landing.